Scheduling the blended solution as industrial CO2 absorber in separation process by back-propagation artificial neural networks - Abdollahi, Yadollah; Sairi, Nor Asrina; Mohd Said, Suhana; Abouzari-lotf, Ebrahim; Zakaria, Azmi; Mohd Sabri, Mohd Faizul; Islam, Aminul; Alias, Yatimah (Elsevier, 2015)
It is believe that 80% industrial of carbon dioxide can be controlled by separation and storage technologies which use the blended ionic liquids absorber. Among the blended absorbers, the mixture of water, N-methyldiethanolamine (MDEA) and guanidinium trifluoromethane sulfonate (gua) has presented the superior stripping qualities. However, the blended solution has illustrated high viscosity that affects the cost of separation process. In this work, the blended fabrication was scheduled with is the process arranging, controlling and optimizing. Therefore, the blend’s components and operating temperature were modeled and optimized as input effective variables to minimize its viscosity as the final output by using back-propagation artificial neural network (ANN). The modeling was carried out by four mathematical algorithms with individual experimental design to obtain the optimum topology using root mean squared error (RMSE), R-squared (R2) and absolute average deviation (AAD). As a result, the final model (QP-4-8-1) with minimum RMSE and AAD as well as the highest R2 was selected to navigate the fabrication of the blended solution. Therefore, the model was applied to obtain the optimum initial level of the input variables which were included temperature 303–323 K, x[gua], 0–0.033, x[MDAE], 0.3–0.4, and x[H2O], 0.7–1.0. Moreover, the model has obtained the relative importance ordered of the variables which included x[gua] > temperature > x[MDEA] > x[H2O]. Therefore, none of the variables was negligible in the fabrication. Furthermore, the model predicted the optimum points of the variables to minimize the viscosity which was validated by further experiments. The validated results confirmed the model schedulability. Accordingly, ANN succeeds to model the initial components of the blended solutions as absorber of CO2 capture in separation technologies that is able to industries scale up.